Features of family-teacher interaction in the formations of students' socio- economic value orientations - Mnaidarova, Svetlana; Shuzhebayeva, Arzigu; Nagymzhanova, Karaka (Espacios, 2017)
The aim of the article is to study family-teacher interaction in the formation of students’ socio-economic value orientations, to create an effective model of formation of students' socio-economic values of a successful person by means of family-teacher interaction. A positive dynamic system of socio-economic value orientations enables young people to realize their professional potential successfully in the context of socio-economic transformations of modern society. They determine the expectations of the society and the employer and, therefore, the objectives of secondary vocational education. An effective family-teacher interaction is one of the major factors in the formation of socio-economic value orientations of a successful person. The study has developed and tested the universal correctional-development program for students, teachers and parents, which consists of training sessions with methods of play therapy, psychological jogging and group discussions, as well as methodological recommendations for parents. The effectiveness of the developed program is confirmed by experimental data that show optimizing family education, increasing psychological and pedagogical competence of parents, as well as the positive impact of the program on the formation of effective students' socio-economic value orientations. The experimental results confirm the practical importance of the developed correctional-development program and its practicability in the educational practices in order to optimize the communication between the family and teaching staff in the process of students’ economic socialization.
Características de la Interacción Familia-Maestro en la Formación de la Orientación de los Valores Socioeconómicos de los Estudiantes
Статья посвящена проблеме формирования социально-экономических ценностных ориентаций студентов в технических и профессиональных образовательных организациях, рассматривается взаимодействие родителей и студентов. подготовка кадров в системе учреждений среднего профессионального образования приобретает особое значение, так как именно эта система способна готовить специалистов разного уровня квалификации. Содержательно-процессуальное построение процесса формирования социально-экономических ценностных ориентаций студентов в технических и профессиональных образовательных организациях должно осуществляться таким образом, чтобы учитывались закономерности развития личности. Построение учебного сотрудничества требует создания таких ситуаций, которые блокируют возможность действовать репродуктивно и обеспечивают поиск новых способов действия и взаимодействия. Только через освоение ценностных норм происходит совершенствование специалиста. В процессе профессиональной подготовки специалиста необходимо принимать во внимание различные социально-экономические общественные трансформации, т.к. именно они напрямую отражаются в ожиданиях общества и работодателя и соответствующим образом влияют на цели среднего профессионального образования. Сформированная позитивная динамическая система ценностных ориентаций позволяет молодым людям конструктивно преодолевать кризисы, способствует успешному освоению профессиональной деятельности и личностному росту в целом. Экспериментальные результаты подтверждают практическую важность разработанной программы коррекционно-развивающей программы и ее практичности в образовательной практике в целях оптимизации связи между семьей и преподавательским составом.
Keywords: Personality development; family-teacher interaction; vocational education; economic socialization; vocational preparation; Развитие личности; процесс формирования ценностных ориентаций; воспитательный процесс; технические и профессиональные образовательные организации; социально-экономические ценностные ориентации; профессиональная подготовка